2003
DOI: 10.1242/dev.00797
|View full text |Cite
|
Sign up to set email alerts
|

Tbx5specifies the left/right ventricles and ventricular septum position during cardiogenesis

Abstract: Extensive misexpression studies were carried out to explore the roles played by Tbx5, the expression of which is excluded from the right ventricle (RV) during cardiogenesis. When Tbx5 was misexpressed ubiquitously,ventricular septum was not formed, resulting in a single ventricle. In such heart, left ventricle (LV)-specific ANF gene was induced. In search of the putative RV factor(s), we have found that chick Tbx20 is expressed in the RV, showing a complementary fashion to Tbx5. In the Tbx5-misexpressed heart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
139
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 62 publications
7
139
1
2
Order By: Relevance
“…The atrial and ventricular septal defects associated with HOS and the phenotype of tbx5 heterozygous mutant mice are consistent with a critical role for Tbx5 in cardiac septation (Bruneau et al, 1999). The restricted expression of tbx5 in the left but not right ventricles is hypothesized to control the position of the ventricular septum (Takeuchi et al, 2003). Although it has been demonstrated that Tbx5 is required for normal septation, the downstream targets regulated by Tbx5 during septation are not fully characterized.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The atrial and ventricular septal defects associated with HOS and the phenotype of tbx5 heterozygous mutant mice are consistent with a critical role for Tbx5 in cardiac septation (Bruneau et al, 1999). The restricted expression of tbx5 in the left but not right ventricles is hypothesized to control the position of the ventricular septum (Takeuchi et al, 2003). Although it has been demonstrated that Tbx5 is required for normal septation, the downstream targets regulated by Tbx5 during septation are not fully characterized.…”
Section: Discussionmentioning
confidence: 91%
“…Experiments eliminating or ectopically expressing tbx5 at these stages suggest a role for Tbx5 in cardiac chamber specification and morphogenesis (Liberatore et al, 2000;Bruneau et al, 2001). Investigation of Tbx5 function by genetic manipulation in mice has demonstrated a requirement for Tbx5 in atrial and ventricular septation, a process that is also disrupted in HOS (Bruneau et al, 2001;Takeuchi et al, 2003). Mice heterozygous null for tbx5 display atrioventricular block, a disruption in conduction system function that resembles what is observed in HOS (Bruneau et al, 2001;Moskowitz et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Another nearby gene, TBX5, plays important roles in chamber formation, septation and cardiomyocyte differentiation 25 . Both gain-and loss-of-function experiments on Tbx5 have resulted in abnormal heart phenotypes in animal models, such as looping defects, loss of the ventricular septum and arrested development of the AV cushions, hypoplastic sinoatrial region and left ventricle 26,27 . The polymorphisms in the upstream region potentially influence the transcriptional activity, and the haplo-insufficiency of TBX3 and TBX5 has also been proven to be associated with CHD 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Atrialization of gene expression in the ventricle may also play a role in the distended RV phenotype observed in the hearts of Hrt2 CKO mice. It is interesting to note that retrovirus-mediated misexpression of Tbx5 in the presumptive RV results in a shift of the interventricular septum to the right and a distended and hypoplastic RV (33). The abnormal RV phenotype accompanying the ectopic expression of atrial-enriched genes, especially Tbx5 in the LV of Hrt2 CKO mice, may suggest a role for Hrt2 in the specification or maturation of the RV and LV.…”
Section: Discussionmentioning
confidence: 99%